To each his own: no evidence of gyrodactylid parasite host switches from invasive poeciliid fishes to Goodea atripinnis Jordan (Cyprinodontiformes: Goodeidae), the most dominant endemic freshwater goodeid fish in the Mexican Highlands. Issue 1 (December 2016) - Rubio-Godoy, Miguel; Razo-Mendivil, Ulises; García-Vásquez, Adriana; Freeman, Mark; Shinn, Andrew; Paladini, Giuseppe
Abstract Background Goodeid topminnows are live-bearing fishes endemic to the Mexican Highlands (Mesa Central, MC). Unfortunately, in the MC, environmental degradation and introduced species have pushed several goodeid species to the brink of extinction. Invasive fishes can introduce exotic parasites, and the most abundant goodeid, blackfin goodeaGoodea atripinnis Jordan, is parasitised by six exotic helminths. Poeciliids are widely dispersed invasive fishes, which exert negative ecological effects on goodeids. Poeciliids host several species of the monogenean genusGyrodactylus von Nordmann, 1832, including pathogenic, invasive parasites. Here, we looked for evidence ofGyrodactylus species switching hosts from poeciliids to goodeids. Methods Fish were collected in rivers draining the MC into both sides of the continental divide. Hosts were screened for gyrodactylid parasites in localities whereG. atripinnis and poeciliids occurred sympatrically.Gyrodactylus specimens were characterised morphologically (attachment apparatus) and molecularly (internal transcribed spacer region, ITS). A Bayesian phylogenetic tree using ITS sequences established relationships between gyrodactylids collected from goodeid fishes and those from parasites infecting poeciliids. Results Gyrodactylids were collected fromG. atripinnis in six localities on both sides of the watershed where exotic poeciliids occurred sympatrically. Morphological and molecular analyses indicated the presence of four undescribed species ofGyrodactylus infecting this goodeid host.Gyrodactylus tomahuac n. sp., the most abundant and geographically widespread species, is described here. The other threeGyrodactylus spp. are not described, but their ITS sequences are used as molecular data presented here, are the only available for gyrodactylids infecting goodeid fishes. Morphological and molecular data suggest that two distinct groups of gyrodactylids infect goodeids, one of which shares a common ancestor with gyrodactylids parasitizing poeciliids. Conclusions No evidence was found of gyrodactylids switching hosts from invasive poeciliids to endemic goodeids, nor vice versa. Moreover, considering thatG. atripinnis is known to host bothGyrodactylus lamothei Mendoza-Palmero, Sereno-Uribe & Salgado-Maldonado, 2009 andGyrodactylus mexicanus Mendoza-Palmero, Sereno-Uribe & Salgado-Maldonado, 2009, with the addition ofG. tomahuac n. sp. and the three undescribedGyrodactylus spp. reported, at least six gyrodactylids may infect this host. This would make monogeneans the second most abundant parasite group infectingG. atripinnis, which to date is known to harbour 22 helminth species: nine digeneans, five nematodes, four cestodes, three monogeneans and one acanthocephalan.